Effective and sustainable prevention and control of pork tapeworm diseases in humans and pigs in Tanzania: a policy brief - Ngowi, Helena A.; Makingi, George; Mlowe, Fredy; Wilson, Christina; Kajuna, Flora; Kabululu, Mwemezi; Churi, Ayubu; Nyangi, Chacha; Nanyaro, Mary-Winnie; Melkiory, Innocent; Nonga, Cosmas; Matembo, Shanel V.; et al. (Frontiers in Tropical Diseases, 2025)
Pork tapeworm (Taenia solium) is a parasite that causes serious diseases in humans and pigs. The parasite causes epilepsy in humans and is estimated to be responsible for approximately 212 deaths per year in Tanzania. The parasite costs Tanzanian society approximately USD 8 million annually due to costs for management of epilepsy caused by the parasite (USD 5 million) and losses due to condemnation of infected pork (USD 3 million). Pork tapeworm diseases are currently not a control and prevention priority in Tanzania, and collaborative efforts among relevant sectors at various levels are limited. This policy brief recommends a One Health approach for effective and sustainable control of the pork tapeworm diseases. It puts forward fourteen actionable recommendations for the country to achieve this goal